The Significance and Motif of Lombok Weaving : A Comparative Analysis of Tradisional and Automated Machine Techniques as a Culture Diversity Learning - Elnawati Elnawati; deviana mayasari; zedi muttaqin (Lembaga penelitian dan pengabdian kepada Masyarakat, 2024)
Handwoven fabrics, commonly known as